(untitled) (Journal of the College of Basic Education, 2023)
The research includes the synthesis and identification of the mixed ligands complexes of M+3 Ions in general composition ,[M(Leu)2(Q)] Where L-leucin (C6H13NO2)symbolized as( Leu H) as a primary ligand and 8-hydroxyqinoline,(C9H7NO) symbolized as (8-HQ) as a secondary ligand . The ligands and the metal chlorides were brought in to reaction at room temperature in ethanol as solvent. The reaction required the following molar ratio [(1:1:2)(metal): Q-:2Leu-] with M(III ) ions, were M(III) = Fe (III ),Cr (III) La(III)) and Ru(III ) The reaction gave solid crystalline complexes which have been characterized us the following techniques: Thermal stability, Solubility, Molar conductivity, Determination the percentage of the metal in the complexes by (AAS). Spectroscopic Methods [FT-IR and UV-Vis], and. The proposed structure of the complexes using program, chem. office 3D(2006) .], Biological effects for some complexes were investigated . Numerous papers have been published on metal complexation of amino acids and derivatives during the past ten years. Metal amino acid complexes have long been of interest as models for metal –Ligand systems and interaction which may occur in nature(1)Biological importance of several amino acids their complexes with transition metals is well documented(2-3)The amino acid L- leucin and various transition metals are important in the biological functions of humans, animals, and plants. L- leucine is one of the twenty major amino acids and is considered an essential amino acid (4) 8-hydroxyqinoline or 8-qinolineis an organic compound with the formula C9H7NO2 is the name most commonly used ,while its trivial name is (oxine),which is conventionally used for the description of chelate compounds Oxinates ,as out of seven possible hydroxyqinoles, only 8-hydroxyqinoline forms chelate with metal ions . [5-6] Ruthenium polypyridyl and phenanthroline complexes have been extensively investigated because of their interesting photochemical[7],catalytic [8], biological [9] and electrochemical [10,11] properties. Lanthanide(III) carboxylates have been widely studied in recent years due to their physico-chemical properties, variety of structural types and potential uses as fluorescent sensors. The isomers of mono-,di- and trimethoxybenzoates of rare earth elements(III) have been examined. [12-13] A series of ruthenium metal complexes involving mono-sulfonylated non-innocent o-phenylenediamine ligands have been characterized in detail using NMR, MS, FT-IR, X-Ray, UV-vis and electrochemical studies. [14] In this paper we present the synthesis and study of Cr(III),Fe(III) La(III) and Ru(III) complexes with amino acid (L-leucin) as a primary ligand and 8-hydroxyqinoline as a secondary ligand have been used, respectively.